Preparación de derivados de verbenona a partir del pinenaldehído - Mendoza Leyva, Luis (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
From pinenaldehyde 3, pinenol 4 was prepared by selective reduction of aldehyde carbonyl group. Reactivity of hydroxyl group in C-9 was analyzed. Esterification reactions of the hydroxyl group in C-9 was explored using chlorides acids of different chemical nature and different volumes, yielding 5, 6 and 7 derivatives. On the other hand, the monosubstituted double bond present in 4, was subjected under epoxidation conditions with mCPBA, obtaining only the epimeric oxepanes 8 and 8a, by intramolecular cyclization in a single-step reaction. Oxepane 8 crystalized from EtOAc, these crystals were suitable for analysis by X-ray diffraction, which, the absolute configuration of its stereogenic center C-7 was assigned applying internal chiral reference criterion. To achieve the epoxidation of this double bond, it was necessary to block the hydroxyl group previously, obtaining the epoxyacetates 10 and 10a. Establishing that these compounds are reaction intermediates for getting 8 and 8a. Testing of 4 under acidic conditions was resumed; finding and optimizing the right conditions to promote its molecular rearrangement, obtaining tetrahydropiran derivative 11. A reaction mechanism based on the hydroxymethylene in C-10 isotopic labeling, was proposed. Finally, in order to obtain verbenone derivatives, mesylate 19 was prepared, from which cis-dimethylallylverbenol 20, dimethylallylverbenone 21 and the mixture of epoxides of dimethylallylverbenone 22 and 22a were obtained.

A partir del pinenaldehído 3 se preparó el pinenol 4 reduciendo selectivamente el carbonilo de aldehído. Se estudió la reactividad del hidroxilo en C-9 de 4, frente a cloruros de ácido de diferente naturaleza química y volumen, los cuales, dieron lugar a los ésteres 5, 6, 7 y 19. Por otro lado, el enlace doble monosustituido de 4 se sometió bajo condiciones de epoxidación con AMCPB, obteniéndose únicamente los oxepanos epiméricos 8 y 8a mediante ciclación intramolecular en un solo paso de reacción. El oxepano 8 cristalizó de AcOEt, obteniendo cristales adecuados para su análisis por difracción de rayos X, asignando la configuración absoluta de su centro estereogénico C-7, aplicando el criterio de referencia quiral interna. La epoxidación del enlace doble en cuestión, se logró al bloquear previamente el hidroxilo de 4, generando los epoxiacetatos 10 y 10a. Estableciendo que estos compuestos son intermediarios de reacción para obtener 8 y 8a. Por otra parte, se retomó el estudio de 4 bajo condiciones ácidas, encontrando y optimizando las condiciones adecuadas para promover su reordenamiento molecular, obteniendo el derivado de tetrahidropirano 11. Se propuso un mecanismo de reacción apoyado por marcaje isotópico del hidroximetileno en C-10. Por último, con el objetivo de obtener derivados de verbenona, se preparó el mesilato 19, del cual se obtuvieron el cis-dimetilalilverbenol 20, la dimetilalilverbenona 21 y la mezcla de epóxidos de la dimetilaliverbenona 22 y 22a.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2018-0704; Esterificaciones; Oxaciclos; Reordenamiento; Dimetilalilverbenona; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2296